2017
DOI: 10.14260/jemds/2017/1402
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Coagulation Markers With Axillary Lymph Node Metastasis in Carcinoma Breast

Abstract: BACKGROUNDThe relationship between malignancy and thrombosis is known for over 100 years. Thrombocytosis, an increase in fibrinogen and fibrin degradation products like D-dimer arise in factors V, VII, VIII, IX and XI levels and a decrease in antithrombin III are seen in cancer patients. Extracellular remodeling of fibrin is essential for angiogenesis in tumours and activation of intravascular fibrin formation and degradation has been shown to occur in the plasma of breast cancer patients. The objectives of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…We found significant relationship between D-dimer and Factor VII and VIII levels and number of lymph nodes involved pathologically. Our study further confirms the similar findings of other studies done by Khangarot et al, Choudhary et al, Yigit et al and Blackwell et al 9,11,12,14 Yigit et al showed this relationship to be significant only when number of lymph nodes is more than 10. 11 As axillary lymph node involvement is most important prognostic factor, this relationship inspires confidence in suggesting D-dimer along with factor VII and VIII levels as prognostic factors, further these factors may be used in those patients who are node negative for an individualized assessment and use of systemic therapy.…”
Section: Relationship With Histological Characteristicssupporting
confidence: 93%
See 2 more Smart Citations
“…We found significant relationship between D-dimer and Factor VII and VIII levels and number of lymph nodes involved pathologically. Our study further confirms the similar findings of other studies done by Khangarot et al, Choudhary et al, Yigit et al and Blackwell et al 9,11,12,14 Yigit et al showed this relationship to be significant only when number of lymph nodes is more than 10. 11 As axillary lymph node involvement is most important prognostic factor, this relationship inspires confidence in suggesting D-dimer along with factor VII and VIII levels as prognostic factors, further these factors may be used in those patients who are node negative for an individualized assessment and use of systemic therapy.…”
Section: Relationship With Histological Characteristicssupporting
confidence: 93%
“…There was no statistically significant difference found between either D-dimer or factor VII & VIII levels according to increase in tumor size. Similar results were also seen in another study done by Choudhary et al 14 In contrast to our result, Blackwell et al showed a significant correlation between tumor size and D-dimer levels. 12 This may be because of the greater sample size in their study group and the large variance possible in mean tumor size.…”
Section: Relationship With Histological Characteristicssupporting
confidence: 90%
See 1 more Smart Citation